(untitled) (Revista Lusófona de Educação, 2025)
The aim of our research was to understand how Initial Teacher Education (FIP) in Portugal is structured, especially in relation to training teachers to respond to diversity, according to the principles of inclusive education (EI). The aim is to understand how Higher Education Institutions (IES) are training teachers of the 1st and 2nd Cycles of Basic Education (CEB) to promote the inclusion of all students, regardless of their condition. To this end, we surveyed the study plans of the Higher Education Schools (ESE) and Public Universities in Portugal and interviewed nine professionals from two IES. This research, which is part of the qualitative paradigm, used the multiple case study methodology. The data was collected by analyzing the legal diplomas, the study plans of the IES and the curricular unit sheets (FUC) of the courses investigated. We concluded that the syllabuses focus more on students’ disorders than on inclusive practices and the need for differentiation for effective participation. Participants indicate that FIP courses are not adequately training future teachers to apply the principles of EI. This is especially relevant since it is the trainers themselves who emphasize this shortcoming. Keywords: Initial Teacher Education, Inclusive Education and Special Educational Needs.